Back to basics with active lifestyles: exercise is more effective than metformin to reduce cardiovascular risk in older adults with type 2 diabetes - Liliana C. Baptista; Aristides M. Machado-Rodrigues; Raul A. Martins (Biology of Sport, 2018)
To establish the effect of three types of treatment – multicomponent exercise (MEX); the oral hypoglycaemic drug metformin (MET); combined therapy comprising exercise plus metformin (MEXMET) – on cardiovascular risk in older adults with type 2 diabetes (T2D) and with comorbidities in an early stage of the disease (HbA1c < 7.5%). A sample of 284 participants was evaluated for multifactorial cardiovascular risk at baseline and at 24-month intervention according to anthropometric and hemodynamic components, lipid profile, glycaemia and cardiorespiratory fitness (CRF). Participants underwent one of three conditions: MEX (n = 59), training in three sessions per week; MET (n = 30), using metformin 850 mg twice daily; MEXMET (n = 195), combining exercise and metformin. After the 24-month intervention MEX and MEXMET showed more positive results than MET therapy. MEX decreased body mass (BM; 4%), waist circumference (WC; 4%), body mass index (BMI; 3%), systolic blood pressure (SBP; 11%), diastolic blood pressure (DBP; 11%), triglycerides (21%), and glycaemia (12%), and increased cardiorespiratory fitness (CRF; 18%). Conversely, the MET group showed increased WC (2%), waist-to-hip ratio (WHR) (3%), and SBP (5%). Differences between MEX and MET groups presented large effect sizes for BM, WC, WHR, SBP, DBP and CRF, and moderate effect sizes for BMI and glycaemia. MEX was the most effective therapy in decreasing cardiovascular risk in the early stage of T2D in older adults with multimorbidity and attenuated the adverse effects of pharmacological therapy in MEXMET treatment.